(untitled) (Applied Biological Research, 2020)
The changes in fishery yield owing to the exponential and logistic growth of non-native tilapia Oreochomi niloticus, was studied and its concrete and predictive invasion worked out so as to find out future level of invasion and yield from the Ganga river, India. The results showed that the abundance of O. niloticus ranged from 3.07 to 15.05% during 2009 to 2018 which increased continually at eight studied locations. At the same time, the average biomass yield day-1 also increased significantly (p < 0.05) in the same period. The calculated mean abundance by weight (MAW) showed that the average biomass was 51.95 kg day-1 km-1 during 2009 which increased to 151 ± 3 kg day-1 km-1in 2018 showing 292% rise within a decade. The biomass-dependent tilapia population revealed significant (p < 0.05) increase in exponential and logistic growth over the years even in the degraded water quality having higher BOD and COD. The predicted increase in the mean abundance by weight-based biomass showed significant change and the annual-regression was p < 0.419 considering the incremental exponential and logistic growth. The predictive forecast of invasive tilapia catches for the period of 2018 to 2028 at 95% confidence limit suggests stable production from the Ganga river inviting attention of scientists and managers towards its management.